Identification of a prognostic risk-scoring model and risk signatures based on glycosylation-associated cluster in breast cancer - Gao, Shengnan; Wu, Xinjie; Lou, Xiaoying; Cui, Wei (Frontiers in Genetics, 2022)
Breast cancer is a heterogeneous disease whose subtypes represent different histological origins, prognosis, and therapeutic sensitivity. But there remains a strong need for more specific biomarkers and broader alternatives for personalized treatment. Our study classified breast cancer samples from The Cancer Genome Atlas (TCGA) into three groups based on glycosylation-associated genes and then identified differentially expressed genes under different glycosylation patterns to construct a prognostic model. The final prognostic model containing 23 key molecules has achieved exciting performance both in the TCGA training set and testing set GSE42568 and GSE58812. The risk score also showed a significant difference in predicting overall clinical survival and immune infiltration analysis. This work helps us to understand the heterogeneity of breast cancer from another perspective and indicated that the identification of risk-scores based on glycosylation pattern has potential clinical implications and immune-related value for breast cancer.